Molecular Dynamics Simulations of Iron-Joining Using Copper as a Filler Metal - Munaji, Munaji; Buntoro, Ghulam Asrofi; Purniawan, Agung; Arifin, Rizal (Makara Journal of Science, 2018)
The study of theliquid filler metal infiltration on the narrow channel of adjoining metal bears importance in understanding the mechanism of the metal brazing process. In this study, we employed the molecular dynamics simulation to understand the mechanism of Cu liquid infiltration through the narrow channel of Fe slabs. Our simulation showed that the wetting process of Fe surfaces by Cu liquid precedes the infiltration process. This study also revealed that the channel became narrower and blockages were found in the channel due to the deformation of Fe surface. In addition to the effect of viscous drag, this process should also contribute to the decreasing speed of the Cu liquid front.